Methodological approaches and algorithms for ranking investment priorities in the sphere of building materials and products, optimization of structure and capital investments - PREDUN, Kostyantyn; HUDOV, Valerii; KOCHUMA, Volodymyr; TSAI, Mykola (Ways to Improve Construction Efficiency, 2025)
The article pays considerable attention to the issues of risk assessment and their minimization in the process of investing in the production of building materials and products. Taking into account macroeconomic trends, the cyclical nature of the construction industry and changes in legislative regulation allows for the formation of informed decisions regarding the priority of financing certain areas. A multifactor analysis model is proposed, which combines financial, production-technological and market indicators to assess the prospects of investments in specific segments of the construction industry. Modern approaches to the automation of investment planning processes and the use of digital tools to predict the effectiveness of capital investments are considered. The use of Big Data technologies, analytical platforms and machine learning algorithms allows to increase the accuracy of forecasting demand for building materials, optimize resource use and reduce logistics costs. The environmental component of the investment process plays a significant role in ensuring sustainable development of the construction industry. The article analyzes the criteria for environmental efficiency of building materials and ways to stimulate investment in energy-efficient and environmentally friendly technologies. The possibilities of attracting state support, international environmental funds and "green financing" mechanisms for the development of innovative projects in the field of construction production are considered. The concept of strategic investment management is proposed, which involves the creation of an integrated system for assessing investment priorities based on a combination of financial, technological and socio-economic factors. This approach ensures optimal allocation of resources, helps to increase the financial stability of enterprises and minimizes the risks of ineffective investment. The results of the study can be useful for a wide range of participants in the construction market, including investors, developers, financial institutions and state regulators. The use of the proposed methodological approaches will increase the level of validity of investment decisions and contribute to the formation of a sustainable investment strategy in the construction sector.